PENGARUH PENDAPATAN ASLI DAERAH (PAD), DANA ALOKASI UMUM (DAU), DANA ALOKASI KHUSUS (DAK) TERHADAP PRODUK DOMESTIK REGIONAL BRUTO (PDRB) KABUPATEN/KOTA DI PROVINSI JAWA TIMUR - Ardiani Maulidia Oktafia; Aris Soelistyo; Zainal Arifin (Jurnal Ilmu Ekonomi JIE, 2018)
This study aims to know the overview of the region original income (PAD), General Allocation Fund (DAU), Specific Allocation Fund (DAK) at Regency / City of East Java Province and to find out how much influence of Local Own Revenue (PAD), General Allocation Fund (DAU), Specific Allocation Fund (DAK) to the Gross Regional Domestic Product (PDRB) at Regency / City of East Java Province on 2012-2016. Gross Regional Domestic Product (PDRB) was used by the dependent variable, while the independent variables were region original income (PAD), General Allocation Fund (DAU), Specific Allocation Fund (DAK). The method of data analysis used by the researcher was the multiple linier regressions method which used the panel data on 2012-2016, It was strengthened by the middle Conformity Test, Statistic test, Coefficient of Determination.The result of the research showed that the PDRB ADHK on 2012 up to 2016, the highest income was in the Surabaya city while the lowest income located in Blitar City. And the result of simultaneous test showed that the whole variables of region Original Income (PAD), General Allocation Fund (DAU), Specific Allocation Fund (DAK) had the positive effect significantly on the Gross Regional Domestic product (PDRB) to the Regency / City of East Java Province.Keywords: DAK, DAU, PAD and PDRB